Competences in English - Nanik Shobikah (Journal of Research on English and Language Learning (J-REaLL), 2020)
This article discusses kinds of English competences. In this article also discusses about the English language skills and components of English language use as the indicator of the student’s competence. The competences of language learning are in the means of communicative competence. To reach those competences, the students must be taught and trained English language in written and oral language skill. Acquiring English as international language is the main indicator of English learning success for students. This article uses qualitative research with a literature study. The data sources are taken from textbooks, journals, articles, research finding, internet articles, newspapers, magazines, etc. The objective of this studies that the result can develop the learner’s understanding about the competences in English language as the basic for the learner in learning and studying English language as the second or the foreign language in Indonesia. The finding shows that the communicative competence (communicative competences relates to the learner’s ability in using language established by language knowledge, skills, and attitude including grammatical, sociolinguistic, discourse, and strategic competence) and the components of English competences (listening, speaking, reading, writing, grammar, vocabulary, and pronunciation) are must be learnt and studied by the students integrative.